PCAF Accelerates Vascular Senescence via the Hippo Signaling Pathway. (6th October 2022) - Kong, Chaohua; Wang, Dongchen; Wang, Feng; Lv, Yifei; Zhou, Wenying; Ye, Peng; Gu, Yue; Jiang, Xiaomin; Zhu, Linlin; Ge, Zhen; Chao, Yuelin; Chen, Shaoliang
Abstract : P300/CBP-Associated Factor (PCAF), one of the histone acetyltransferases (HATs), is known to be involved in cell growth and/or differentiation. PCAF is reported to be involved in atherosclerotic plaques and neointimal formation. However, its role in cellular senescence remains undefined. We investigated the potential mechanism for PCAF-mediated cellular senescence. Immunohistochemical (IHC) analysis showed PCAF was distinctly increased in the endothelia of aorta in aged mice. Palmitate acid (PA) or X radiation significantly induced the expression of senescence-associated markers and PCAF in human umbilical vein endothelial cells (HUVECs). PCAF silence in PA-treated HUVECs significantly rescued senescence-associated phenotypes, while PCAF overexpression accelerated it. Additionally, our results showed that Yes1 Associated Transcriptional Regulator (YAP) that acts as end effector of the Hippo signaling pathway is crucial in PCAF-mediated endothelial senescence. YAP activity declining was observed in aged vascular endothelia. Overexpression of YAP partially ameliorated PCAF-induced endothelial senescence. In vivo, endothelial-(EC-) specific PCAF downregulation in aged mice using adeno-associated virus revealed less vascular senescence-associated phenotypes. These results suggested that PCAF mediated endothelial senescence through the Hippo signaling pathway, implying that PCAF may become a potential target for the prevention and treatment of vascular aging.